Indeks Tenunan Tradisional Minangkabau Koleksi Museum Adityawarman - Ayunda, Rahmadini Putri; Desriyeni, Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
In this paper discussed about how to manufacture traditional Minangkabau woven index in Adityawarman Museum collection. The aim of this paper is to help visitors and manager of museum to surf the information. In this paper described the stage of making traditional woven index collection in  Adityawarman Museum. The method used in this  paper is descriptive method done by direct observation and interviews with the manager of the museum. The observations were made by collecting and recording data from the woven collection at traditional  Adityawarman Museum. Based on direct observation of woven collection in Adityawarman Museum are 357 collections. Based on the discussion above, the researcher can concluded the stage of making traditional Minangkabau woven index are as follows: (1) screening a collection of Minangkabau traditional weaving; (2) create a description of the article that the collection of the name, place of origin collections made in, from the collection of woven materials, the inclusion of the collection, the size of weaving, as well as a collection of code and registration number that has been determined by the museum; (3)  provisions which comply with the rules of index typing; (4) Typing index woven collection.Keywords: Index, weave, Minangkabau, Museum Adityawarman.